A Pt-free Electrocatalyst Based on Pyrolized Vinazene-Carbon Composite for Oxygen Reduction Reaction. (10th April 2015) - Akinpelu, Akeem; Merzougui, Belabbes; Bukola, Saheed; Azad, Abdul-Majeed; Basheer, Rafil A.; Swain, Greg M.; Chang, Qiaowan; Shao, Minhua
Abstract: The 2-vinyl-4, 5-dicyanoimidazole (Vinazene) was used as a nitrogen precursor to synthesize a promising non-precious metal (NPM) catalyst for oxygen reduction reaction (ORR). Vinazene together with an iron source was impregnated into a carbon matrix and pyrolyzed at 900 °C in N2 atmosphere. The structure of the resulting Fe–N–C nanocomposite was analyzed by X-ray photoelectron spectroscopy, Raman spectroscopy and X-ray diffraction. Both rotating disk electrode (RDE) and rotating ring-disk electrode (RRDE) experiments showed excellent ORR activity for the obtained catalyst with low H2 O2 formation (∼3.0%) in 0.1 M KOH. The catalyst was found to be rich in mesoporous structure along with high percentage of pyrrolic-N function with surface area of about 673 m 2 g −1 and pore size of 4.2 nm. In addition to its excellent ORR activity, the catalyst showed remarkable tolerance towards methanol oxidation and demonstrates good stability over 10, 000 potential cycles (0.6–1.0 V Vs RHE). We believe that this N-rich Vinazene molecule will be beneficial to further development of nitrogen doped carbon electrocatalysts.